Men of honor - De Niro, Robert; Gooding, Cuba, 1968-; Holbrook, Hal.; Theron, Charlize; Tillman, George, 1969-; Smith, Scott Marshall; Teitel, Robert; Badalato, Bill.; Fox 2000 Pictures; State Street Pictures; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 2001)
The courageous story of an African-American sailor (Gooding) who dared to dream of becoming a U.S. Navy Master Diver. Despite a ruthless training officer (De Niro) and a tragic shipboard accident, Carl's iron will is never broken. Against all odds, he pushes on to achieve the impossible.
"Based upon the life of Carl Brashear."
Originally produced as a motion picture, c2000.
Formatted to fit TV screen.
Music, Mark Isham ; film editor, John Carter with Dirk Westervelt ; director of photography, Anthony B. Richmond.
Robert De Niro, Cuba Gooding, Jr., Aunjanue Ellis, Hal Holbrook, David Keith, Michael Rapaport, Powers Boothe, ... and Charlize Theron.
Rated R.
Keywords: Brashear, Carl M. -- 1931-2006 -- Drama; United States. -- Navy -- African Americans -- Drama; United States. -- Navy -- Petty officers -- Drama; African American sailors -- Drama; Divers -- Drama; Deep diving -- History -- 20th century -- Drama; Films for the hearing impaired; United States -- Armed Forces -- African Americans -- Drama; Feature films; Biographical films